Racial Issues in American Stand-up Comedy - Alina BOGDAN (PETRE) (Cultural Intertexts, 2014)
The phenomenon known as stand-up comedy emerged in the late 1970s when the first live shows of this type were introduced to the public. This type of humour, which relies on ingenuity, contains a variety of topics used by comedians, such as their everyday life, religion, politics or racism. These are just a few of the topics usually employed in order to create comedy. It is curious how a serious matter such as racism, for example, can be used to trigger laughter. Eddie Griffin, an African American stand-up comedian, uses this type of topics in almost all of his shows. More than one question come to mind: Why should comedians use racism in this type of discourse? Can it be funny? Are there any special techniques applied when dealing with such a sensitive subject? Can the humour be preserved if the written version of such a show is translated? The present paper aims at finding some answers to these questions and, to this end, looks for textual evidence in Eddie Griffin’s 2011 comedy show You Can Tell ‘Em I Said It.